The Students' Ability in Pronouncing Long and Short Vowels in English Vocabulary - Ruslan Hasyim; Fatma Fatma; Fitriani Fitriani; Noventy Irianty Tumbel Irianty Tumbel (ITScience (Information Technology and Science), 2022)
Pronunciation test in using the English Pronunciation British application is very important for students but many vocations provide English material that is still general and not specific to the style. This research aimed to determine the students' abilities and mistakes in pronouncing long and short vowels in English vocabulary. The method used in this research is descriptive qualitative. The pronunciation test was used as an instrument for the research. First, a pronunciation test is given to students to read 20 words of vocabulary. Researchers used recordings in the English Pronunciation application to obtain data. Researchers analyzed students' needs using descriptive analysis. According to the research results, the respondent's ability in pronouncing long vowels has a score of 804% and short vowels have a score of 840%. The problem that the respondent is aware of is the pronunciation of long vowels which have a low score. Teachers must be creative enough to design better techniques that can arouse student motivation and encourage students to read more English vocabulary in the pronunciation of long and short vowels.